Bibliometric Analysis in Sulcus Vocalis Research: 44 Years of Perspective - Ture, Nurullah; Tahir, Emel; Murat, Naci (Springer, 2025)
ObjectivesThis study aimed to provide a comprehensive bibliometric overview of the scientific landscape on sulcus vocalis by analyzing publication trends, global research productivity, and thematic evolutions in the literature from 1980 to 2024.MethodsA total of 150 English-language articles and reviews related to sulcus vocalis published between 1980 and 2024 were retrieved from the Web of Science Core Collection. Bibliometric and scientometric analyses were performed using VOSviewer and CiteSpace software. Citation data, keyword co-occurrence, author and institutional collaborations, and country-level networks were evaluated to reveal research trends and influential contributions.ResultsThe annual number of publications showed a significant increase after 2010, peaking between 2019 and 2021. The most prolific countries were the USA (n = 52), Brazil (n = 15), and Japan (n = 14), with the University of Wisconsin and Harvard University identified as the leading institutions. Keyword analysis revealed a historical focus on "medialization laryngoplasty," shifting toward "platelet-rich plasma" in recent years. The Journal of Voice and The Laryngoscope were the most common publication journals. The most cited articles addressed vocal fold biomechanics, diagnostic criteria, and surgical interventions. Network analysis highlighted the USA and Belgium as central actors in international collaboration.ConclusionSulcus vocalis research has evolved into a dynamic, interdisciplinary field integrating clinical, surgical, and regenerative medicine approaches. Despite increased academic output, a lack of consensus on classification and long-term treatment outcomes persists. The findings underscore the need for systematic reviews, novel therapeutic models, and AI-assisted diagnostic tools. This study maps the structure of sulcus vocalis research and provided a foundation for guiding future multidisciplinary and international collaborations.
Türe, Nurullah/0000-0002-1664-5634;
Keywords: Sulcus Vocalis; Bibliometric Analysis; Vocal Fold; Citation Network; Research Trends; Regenerative Medicine; Voice Disorders